REKONSTRUKSI PARADIGMA ILMU PENGETAHUAN UNTUK KEBERLANJUTAN EKOLOGIS - Thohir Yuli Kusmanto (Jurnal Sosiologi Reflektif, 2014)
Humans develop the science and technology that are material and immaterial, for survival in the face of the earth . Science and technology created systemic and functional. It evolved in the span of a long history of human life. However the nature, character, methods and ways of view together in one term called the paradigm. The dynamics of science and technology led to the emergence of various paradigms. In its development, there is always a dominant paradigm, which has a very strong inflence on the system of knowledge and practice in public life. Dominance paradigm determining the nature, character, methods, perspectives, and orientation as well as the expectation of life. Positivism paradigm dominates human life today, in the form of a system or ideology of modernism and the main instrument of industrialization. Modernism man as the central position of life in the universe. Human determine all aspects of life according to the needs, desires and ways of thinking. Science and technology was developed as a means of subduing and controlling the universe. As a result of ecological damage occur everywhere, and causes people to live in misery. Although man created science and technology to solve it. Ecological disaster is diffiult to overcome, as a result of errors paradigmatic. Strategic effort is necessary, with the reconstructed paradigm in science and technology system that has been developed and used by humans